CLASSICAL BALLET PRE-POINTE EDUCATION: AN ANALYSIS OF THE PEDAGOGY FOR THE TRAINING OF YOUNG DANCERS - Taylor-Spann, Rose (My University, 2016)
The concept of preparing young female dancers for pointe work is not new to ballet education; however, attention to specific pre-pointe training has become more focused in recent years. Pre-pointe as a defined course of study within classical ballet training has become more common in programs throughout the United States. Contemporary knowledge in fields such as anatomy, exercise science and pre-adolescent and early adolescent development has motivated dance educators to reexamine the pedagogy of pointe preparation and how students are evaluated for pointe readiness. This consideration has prompted the evolution and prolificacy of pre-pointe specific classes and programs incorporated into American ballet training curriculum. The timeliness of this topic in response to increasing conversations surrounding pre-pointe greatly inspired this project. The importance of pointe preparation and the evaluation of a student’s readiness for pointe work, paired with the abundance of pre-pointe programs motivated the research for this project. Relatively little published information regarding pre-pointe pedagogical methods is currently available to instructors. Limited resources and the ambiguity of pre-pointe training significantly contributed to the development of the research model for this thesis. The purpose of this thesis is to analyze and assess pre-pointe pedagogy in classical ballet training; determine effective and healthful approaches to preparing dancers and evaluate their readiness for pointe; and identify methods for effective communication between dance educators, students and their parents. Codified classical ballet methods were assessed to identify elements of pointe preparation within the technical progression. It was determined that the most effective method of gathering information regarding the questions and problems that inspired this project was to conduct interviews with select dance educators and observe ballet technique, pre-pointe, and pointe classes. Due to the newness of this topic, it was essential to consult current professionals in the field who are teaching classes and developing programs for pre-pointe. Interview questions addressed pre-pointe topics including school and class structure, evaluating student readiness for pointe, and pre-pointe training methods. Subtopics pertaining to pre-pointe training were also considered through the development of this thesis. Areas such as pre-adolescent and early adolescent physical, cognitive, and social development, student wellness, the use of pre-pointe shoes, class observations, and communication between ballet teachers students and parents are presented as they relate to pointe preparation. This thesis presents thorough feedback gathered from interview participants comprised of dance educators representing reputable ballet schools throughout the United States. Information gathered through the research process culminates in recommendations regarding the pre-pointe topics discussed including student wellness, pre-pointe training, evaluating student readiness for pointe, and the importance of class structure and consistent instruction. This document may serve as a resource for dance educators regarding pointe preparation and offers prospective continuing research possibilities.
Keywords: Ballet; Pedagogy; Education; Pointe; Dance; Pre-Pointe